Faktor-Faktor Yang Memengaruhi Aliran Perdagangan Produk Pertanian Antar Negara ASEAN (Forum Agribisnis, 2024)
The agricultural sector has an important role for national economic development, especially countries in the ASEAN region with a climate that is very suitable for agricultural activities. Trade in agricultural products between ASEAN countries in terms of exports has gradually increased, but exports out of the region are very large. The lower export ratio in the ASEAN region can be due to ASEAN's highly competitive agricultural products, but this cannot increase the import ratio between countries. This condition explains that the utilization of opportunities in trade activities in the ASEAN region has not been optimal.  The purpose of the study is to determine the factors that influence the flow of trade in agricultural products between ASEAN countries. The data used by researchers are secondary data in the agricultural sector for the period 2013 to 2022 with variables of GDP of each country in ASEAN, GDP per capita, population, economic distance, and exchange rate. The data is processed with a gravity model approach. The results showed that the independent variables that had a positive and significant effect were the population of the country of origin, population of the partner country, GDP per capita of the country of origin and GDP per capita of the partner country, while economic distance had a negative influence on the model of trade flow of agricultural products between ASEAN countries. To support the flow of trade in agricultural products, it is necessary to rigid port infrastructure development in each country in the ASEAN region by increasing port capacity, port development, and facilities and infrastructure that support the efficiency of the export process and import of agricultural products. Improving the quality of agricultural products needs to be done to be in accordance with the standards of export destination countries and able to compete.